The Effects of Management Accounting Practices on Financial Performance of Manufacturing Small and Medium Enterprises in Zimbabwe - Kwenda, Farai; Harrison, Tendai Florine (The Journal of Accounting and Management, 2025)
Objectives: This study examined the effects of management accounting practices on financial performance of manufacturing small and medium enterprises (SMEs) in Zimbabwe. Prior work: Literature acknowledges that companies fail due to poor financial performance attributed to under-utilisation of management accounting practices. Consequently, management accounting has a role in strategic decision-making and enhancing organizational performance and are key drivers to economic development and growth. Approach: The study analyzed the adoption of informal, traditional and contemporary management accounting practices and integration of practices. The study adopted a quantitative research approach and a cross-sectional survey research design. The study utilized primary data collected through online questionnaires from 315 manufacturing SMEs in Harare, Zimbabwe. Findings/Results: The study found that informal and traditional management accounting practices are widely used compared to contemporary management accounting practices. Significant positive direct relationships among informal, traditional and contemporary management accounting practices and financial performance were found. Study results also show that management accounting practices effects are evident on asset value and revenue turnover of SMEs. Implications: The study concluded that business nature and size affect complexity of management accounting practices used. The use of ccontemporary and informal management accounting practices proffer improved quality, efficiency and competitiveness that responds to global competition. Manufacturing SMEs can leverage management accounting practices to improve their asset value and revenue turnover, ultimately enhancing their overall financial performance. This can be achieved by integrating formal and informal practices and adopting contemporary practices. Value: This study contributes to the management accounting literature by offering strategies on adoption and implementation of management accounting practices by manufacturing SMEs in developing countries and improve sustainability and competitiveness.